1996
DOI: 10.1074/jbc.271.10.5623
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Neurotrophin-3 to p75LNGFR, TrkA, and TrkB Mediated by a Single Functional Epitope Distinct from That Recognized by TrkC

Abstract: Neurotrophins regulate differentiation and survival of vertebrate neurons through binding to members of the Trk family of receptor tyrosine kinases and to a common low affinity receptor, p75 LNGFR. The specificity of neurotrophin action is determined by their selective interaction with the different members of the Trk family; TrkA, TrkB, and TrkC serve as cognate receptors for nerve growth factor, brain-derived neurotrophic factor, and neurotrophin-3 (NT-3), respectively. Unlike nerve growth factor and brain-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 42 publications
(61 reference statements)
3
41
0
Order By: Relevance
“…Also in line with these results are studies on NT-3 where mutants with alanine exchanges of Arg-31 and His-33 were shown to determine the binding site of NT-3 to its nonpreferred receptors TrkA and TrkB. These NT-3 mutants also remained active on the TrkC receptor (53) as is the case with the mutants presented in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Also in line with these results are studies on NT-3 where mutants with alanine exchanges of Arg-31 and His-33 were shown to determine the binding site of NT-3 to its nonpreferred receptors TrkA and TrkB. These NT-3 mutants also remained active on the TrkC receptor (53) as is the case with the mutants presented in this study.…”
Section: Discussionsupporting
confidence: 86%
“…The IC 50 of NT-3 competition of 125 I-NGF binding requires a 250-fold excess of NT-3 to block binding to 4.1 TrkA/B receptors, whereas a 25-fold excess of NT-3 is required to block binding to wild type TrkA receptors (19). These results further confirm the role of TRKA-D5 subdomain in NT-3 binding, and the 10-fold difference in NT-3 binding to TrkA WT and 4.1 TrkA/B chimera indicates that TrkB-D1-D4 subdomains do not compensate for the equivalent subdomains of TrkA.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that NT-3 has a lower affinity interaction with its heterologous receptors TrkA and TrkB (13,19), and that the biological outcomes of NT-3-TrkA interactions are limited (e.g. partial survival, or limited differentiation) (6) suggests three nonexclusive possibilities as follows: (i) NT-3 as heterologous ligand may lack some docking sites on TrkA for high affinity binding and full function; (ii) the interaction may take place through epitopes that are distinct from those used by NGF; and/or (iii) receptor conformational or allosteric regulation by each ligand may be different.…”
mentioning
confidence: 99%
“…Steady-state competitive bindings were performed at 4°C as described previously (34). Saturation bindings were performed in triplicate wells with 10 6 cells/ml and serial dilutions of radioiodinated factors in Dulbecco's phosphate-buffered saline supplemented with 1 mg/ml bovine serum albumin and 1 mg/ml glucose.…”
Section: Methodsmentioning
confidence: 99%
“…Bioassays-Biological activities in TrkA-expressing MG87-NIH3T3 fibroblasts were assayed as described previously (34). Briefly, in a 96-well plate 20,000 cells/well were incubated in serial dilutions of native or mutant NGF in serum-free medium (Dulbecco's modified Eagle's medium).…”
Section: Methodsmentioning
confidence: 99%